TEKNIK ASOSIASI : STRATEGI PESAN DAKWAH DI INSTRAGRAM - Rahma Maemona; Mutia Rahmi Pratiwi (Jurnal Riset Komunikasi (JURKOM), 2020)
The development of social media has an impact on the progress of various things including media in da'wah. Preachers carry out strategies on social media, including emphasizing the appearance of texts with persuasive communication according to their segmentation. This study aims to analyze the da'wah message strategy on the @ nunuzoo instagram page. The theory used is the persuasive communication theory introduced by Onong Uchajana Effendy. This study uses a qualitative description method with a virtual ethnographic approach. Primary data was collected from video uploads on the Instagram account @ nunuzoo and secondary data was collected using literature studies and documentation. The results of this study indicate that @nunuzoo uses the association technique as a da'wah strategy, namely persuading its segmentation with objects or events that are attracting the attention of the public (trend). @nunuzoo has a target of preaching among young people, who like new things and are being discussed. Social media is also better to be used as an alternative media for persuasive communication because it is unlimited and can be accessed anywhere and anytime.